Transformasi Sistem Pertunjukan Jegog Dalam Pariwisata Budaya: Pelestarian Budaya Dan Penguatan Identitas Komunitas Di Desa Adat Kertha Jaya Pendem - I Wayan Sunardi; I Nengah Bawa Atmaja; I Nyoman Raka (Jayapangus Press, 2026)
Jegog, a large bamboo musical ensemble originating from Jembrana, has increasingly expanded from communal performances into cultural tourism. This study examines the factors driving its transformation, the changes in its performance system, and the implications for cultural preservation and community identity in Kertha Jaya Pendem Customary Village. The study employed a qualitative descriptive approach with ethnographic and phenomenological orientations. Data were collected from September to October 2025 through non-participant observation, semi-structured interviews with four key informants, and documentation, and were analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings show that the transformation of Jegog is driven by internal factors, including regeneration, artistic creativity, changing group orientations, and limited resources, as well as external factors such as tourism demand, government facilitation, media exposure, and technological development. The performance system has changed through shorter duration, selective and communicative repertoires, rearranged sequences, faster tempo, strengthened visual choreography, more elaborate costumes and stage settings, shifts in performance spaces, and more interactive audience relations. These changes increase performance opportunities, public recognition, youth participation, and economic benefits, but may weaken cultural meaning when technical skills are transmitted without adequate historical, social, and customary understanding. The main finding is a two-context adaptation model, in which inherited conventions are maintained in customary and communal performances, while controlled innovation is permitted in tourism performances. This model demonstrates that transformation can support cultural preservation when the community retains authority over the boundaries and meanings of change.